Induction and characterisation of the ovine mucosal immune response to rotavirus - VanPinxteren, Laurens Adrianus Hendricus (The University of Edinburgh, 1997)
The local and systemic immune response to rotavirus was investigated, both in previously exposed adult sheep and gnotobiotic lambs.

Vaccines were used parenterally to boost the local and systemic humoral immune response of adult sheep. The response was evaluated by assays for rotavirus (RV)-specific IgA and IgG antibodies and vims neutralising activity (VNT) in serum, nasal secretions, and intestinal scrapings. Sheep vaccinated (n=12) parenterally with a standard rotavirus vaccine (IFA and inactivated rotavirus lysate (low dose)) showed a significant (p<0.05) increase in RV IgA antibodies in nasal secretions and intestinal scrapings 2 weeks after vaccination. Sheep vaccinated (n=4) parenterally with different adjuvants and antigen doses showed both dose-related and adjuvant-related effects in RV IgG antibodies in serum and nasal secretions 2 weeks after vaccination. At a low virus dose, ISCOMs and IFA induced a significantly (p<0.05) higher humoral immune response compared with microspheres, however at a high dose (inactivated purified virus), ISCOMs and microspheres induced a significantly (p<0.05) higher humoral immune response compared with IFA. The immune response after parenteral vaccination is dose- and adjuvant-dependent.

Sheep vaccinated (n=4) orally with live virus, with different adjuvants and antigen doses showed no significantly increased humoral immune response. No dose effect or adjuvant effect was observed.

More extensive techniques were used to characterise the primary immune response in gnotobiotic lambs after infection with a lamb-passaged rotavirus strain K923. Lambs (n=10) were infected at 6 days of age and killed over a 7 week time interval together with controls (n=6). RV antibodies and VNT were determined in serum, nasal secretions, and intestinal scrapings. RV antibody producing cells were enumerated in blood. Lymphocyte populations in blood and GALT were analysed. Lymphocyte proliferations were determined in blood and GALT and cytokine expression was analysed in JPPs and MLNs.

Infected lambs cleared the virus by 8-9 days post-infection without showing any clinical signs. RV IgA antibody-secreting cells (ASC) in blood and RV IgA antibodies in serum and nasal secretions were detected from 7 days after infection v followed at 10 days after infection by RV IgG ASC and antibodies. RV IgA antibodies dominated after an infection with rotavirus. RV IgA antibodies were not detected in intestinal scrapings in the first 10 days after infection, however at 52 days after infection rotavirus-specific IgA antibodies were observed. Lymphocyte proliferation was seen in JPPs at 52 days after infection. No significant changes were observed in lymphocyte sub-populations. IFNy transcripts were expressed in JPPs and MLNs in both groups and infection had no effect on the expression of IFNy. IL-4 transcripts increased with time but the infected group showed a higher expression at 3 and 52 days after infection. The first evidence of an immune response was seen in the increased level of IL-4 3 days after infection, which preceded the presence of RV IgA and IgG antibodies in serum and mucosal surfaces. IL-6 transcripts were expressed and increased with time in the infected groups. No clear evidence for CD8+ T cell or rotavirus-specific secretory antibody involvement in viral clearance was found suggesting that other mechanisms may play a role.

Vaccines composed of either rotavirus mixed with ISCOMs or recombinant VP6 incorporated into ISCOMs were used to examine if one oral dose could induce a mucosal immune response and protection against subsequent challenge. Gnotobiotic lambs were vaccinated orally either with PBS/ISC, inactivated rotavirus (IRV)/ISC, recombinant VP6/ISC, or IRV alone, challenged 3 weeks later with a live lambpassaged strain, and killed 8-9 days after challenge. The immune response was measured as described above. The rotavirus-vaccinated groups had RV IgG ASC and antibodies in blood from 7 and 11 days respectively. After challenge, rotavirusvaccinated groups cleared the virus in a reduced period (7.0 days vs 9.0 days), however this was only significant (p<0.05) in the IRV/ISC group. RV IgA antibodies were observed in serum and nasal secretions from 4 days after challenge. In intestinal scrapings, these were significantly (p<0.05) higher in the IRV/ISC and IRV groups. RV IgG antibodies were significantly (p<0.05) increased in nasal secretions and intestinal scrapings in the IRV/ISC and IRV groups. Lymphocytes from JPPs proliferated significantly against rotavirus in the IRV/ISC and IRV groups. CD45R+ cells were significantly increased in blood in the IRV/ISC group before challenge, however no differences were found in other lymphocyte sub-populations either in blood or GALT. A down-regulation of IFNy transcripts was observed in JPPs and vi MLNs in the IRV/ISC group while the VP6/ISC group had a higher expression compared with the PBS/ISC and IRV groups. IL-4 transcripts were low in MLNs in all groups but in JPPs the rotavirus-vaccinated groups had a higher expression. IL-6 transcripts in JPPs were higher in the IRV/ISC and VP6/ISC groups but in MLNs all rotavirus-vaccinated groups had a higher level of expression. One oral dose of inactivated rotavirus alone, mixed with ISCOMs, or recombinant VP6 incorporated into ISCOMs can induce priming and partial protection. These results suggest also that different immunological mechanisms take place when different vaccination protocols are used.